Implementasi Metode Takrir Untuk Meningkatkan Hafalan Bacaan Shalat Siswa Pada Mata Pelajaran PAI di Kelas III SDN 1 Setungkep Lingsar - Romi Oriza; Zahratul Aini; Nisian Sukriana; Ade Mariana Ayu (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2024)
Education for human life is an absolute life that must be fulfilled throughout life. Without education, a group of people will find it difficult to live and develop in line with their ideals to progress. This research aims to describe how the implementation of the Takrir method in strength students' memorization of prayer readings in PAI subjects at SDN 1 Setungkep Lingsar and to determine the impact of implementing the Takrir method on memorizing prayer readings for grade III students at SDN 1 Setungkep Lingsar. This type of research uses a descriptive qualitative approach. This descriptive qualitative approach is an approach that describes or depicts a problem or event. Data collection was carried out in three ways, namely, observation, interviews, and documentation. Meanwhile, data analysis used data condensation collection techniques, data presentation, and conclusion drawing. In testing the validity of the data using three methods, namely extending observation, increasing persistence, and triangulation. Based on the research results, two things were pound (1) the implementation of the Takrir method to strengthen students' memorization of prayer readings went through 3 stages. Opening, Centauri, and implementation (2) impact implementing the taker method of strengthening memorization of prayer readings are: increased memorization increased fluency, increased persistence, and increased istikomah.